Knowledge management and resilience of urban and territorial systems - Paganin, Giancarlo; Talamo, Cinzia; Atta, Nazly (TECHNE - Journal of Technology for Architecture and Environment, 2018)
The concept of resilience related to the built environment, thus to urban and territorial scales, counts today a multiplicity of declinations and applications: with respect to these scales, the paper deals with the central role of information for the analysis of fragility and vulnerability and for thedevelopment of resilience strategies. Assuming a hierarchical vision of knowledge and considering the current evolution of information technologies, the purpose is to outline innovative knowledge management methods and applications aimed at promoting forms of resilience of social, physical and infrastructural systems. Hitherward, the implications of current technological innovations related to Big Data and IoT (Internet of Things) are also investigated.